Addictive disorders, psychiatric symptoms, and potentially traumatic events in individuals with disabilities - Marín-Navarrete, Rodrigo; Sánchez-Domínguez, Ricardo; Pérez-López, Alejandro; Saracco-Alvarez, Ricardo (Frontiers in Psychology, 2022)
Background/Objectives: Various studies have established that people with disabilities have a greater proportion of potentially traumatic events (PTEs) either in childhood or in adulthood, generating a greater risk of suicide attempts, mental disorders and substance use disorder. In order to examining the prevalence of PTEs, substance use, psychiatric symptoms and suicidal behavior in individual with disability; and determinate the relationship between PTEs with a variable of interest. A Multisite cross-sectional study was conducted. Method: the participants were 1098 individual con any type of disability (motor, intellectual, visual and mixed) located in Mexico City, the data was collected between September-October 2014. Results: People with motor or visual disability have a higher prevalence in nicotine use disorder (NUD), generalize anxiety disorder (GAD), mayor depression disorder (MDD), want to be dead, and attempts to suicidal lifetime. Intellectual disability group only presents GAD and MDD. All disability groups have a high prevalence of PTEs. Verbal violence in childhood, sexual abuse, discrimination and serious accidents had a strong impact on the development of NUD, psychiatric symptoms and suicidal behavior. Conclusions: The findings of this study, derive in the need to have specific tools in the detection, referral and treatment to have an impact significant in the mental health of people with disabilities.